2018
DOI: 10.15171/apb.2018.052
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Stability Assessment of Anti-EpCAM Immunotoxin for Cancer Therapy

Abstract: Purpose: Epithelial cell adhesion molecule (EpCAM) is a dominant antigen in human colon carcinoma tissue. Topology features of this antigen are different in normal and malignant conditions; for instance, EpCAM is much less accessible to antibodies in normal cells than in cancerous tissues. Hence, EpCAM has been considered as a suitable candidate for cancer target therapy via immunotoxins (ITs) development. In this study, attention was focused on the stability assessment of anti-EpCAM-IT (anti-Ep-IT) to design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
1
3
Order By: Relevance
“…Though many studies have modeled EpCAM [ 3 , 10 , 28 , 29 , 30 , 31 ], we have not found reported evidence of the TY loop-CTD binding site. This is understandable given that these studies have mostly focused on predicting EpCAM interactions with therapeutics targeting the physiological cis -dimer form [ 10 , 29 , 31 ].…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Though many studies have modeled EpCAM [ 3 , 10 , 28 , 29 , 30 , 31 ], we have not found reported evidence of the TY loop-CTD binding site. This is understandable given that these studies have mostly focused on predicting EpCAM interactions with therapeutics targeting the physiological cis -dimer form [ 10 , 29 , 31 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Though many studies have modeled EpCAM [ 3 , 10 , 28 , 29 , 30 , 31 ], we have not found reported evidence of the TY loop-CTD binding site. This is understandable given that these studies have mostly focused on predicting EpCAM interactions with therapeutics targeting the physiological cis -dimer form [ 10 , 29 , 31 ]. Likewise, researchers have focused on characterizing other EpCAM domains such as the intramembrane [ 3 ] and intracellular [ 30 ] regions.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…VB4-845 (or oportuzumab monatox, Proxinium) is a recombinant fusion protein that combines the specificity of an anti-EpCAM ScFv with the toxicity of PE 40. [61][62][63] Mesothelin, expressed on mesotheliomas, ovarian, pancreatic, and lung cancers, has been targeted with PE toxin and was found to have a synergistic effect with chemotherapeutic agents in a mice model. 44,49,64 One of the more interesting ITs is SS1P or antimesothelin (Fv)-PE38.…”
Section: Growth Factor Receptors As Targetsmentioning
confidence: 99%